Pengaruh Media Tanam dan Pemupukan terhadap Pertumbuhan Bibit Jambu Biji (Psidium guajava L.) untuk Batang Bawah - I KADEK EKADANA; I NYOMAN RAI; GEDE WIJANA (Fakultas Pertanian Universitas Udayana, 2017)
Effects of Plant Media and Fertilization on The Growth of Guava Seed (Psidium Guajava L.) for The Under Stem. The availability of the rootstock with good growth very important in the Propagation of guava. Improvement of the factors that affect the growth of guava seedlings for rootstock needs to be done to spur its growth. The alternative that can be done is to improve vegetative growth by choosing the right planting medium and good fertilization. The research was conducted on farmers farm located in Banjar Tiyigan, Pelaga Village, Petang, Badung, Bali. The study used factorial randomized complete block design (RCBD). The first factor planting media consists of 4 levels i.e soil+sand, soil+sand+compost, soil+sand+rice husk and soil+sand+compost+rice husk. The second factor fertilization consisting of 3 levels i.e chemical fertilizer (NPK), liquid organic fertilizer (biourine) and NPK+biourine fertilizer, which were repeated 4 times. The results showed that there was no interaction between treatment of planting medium and fertilization. The treatment of planting media had significant effect on all observed variables, except for N and P leaf content. The treatment of fertilizer has a significant effect to the variation of leaf area, leaf plant and plant height. The best planting medium was found on mixed soil+sand+compost+rice husk with total dry weight of oven per plant 11.65 g very different from other media. Meanwhile for the treatment of NPK fertilizer added with biourine fertilizer gave the plant height of 29.04 cm is very different with other fertilizers.